Influência da imunocastração (Bopriva®) no ganho de peso, características de carcaça e qualidade da carne de bovinos Nelore - Andreo, Nayara; Bridi, Ana Maria; Tarsitano, Marina Avena; Peres, Louise Manha; Barbon, Ana Paula Ayub da Costa [UNESP]; Andrade, Evelyn Lopes de; Fernandes Prohmann, Paulo Emilio (Univ Estadual Londrina, 2013)
The objective of this study was evaluate the effects of immunocastration on body weight gain, carcass characteristics and meat quality of Nellore beef cattle. Eighty Nellore beef cattle, with initial body weight of 357 +/- 8.63 kg, were placed in feedlots and distributed in two treatments (40 animals per treatments) as follow: one - non-vaccinated bulls and two - immunocastrated bulls (Bopriva (R), Pfizer Animal Health). The animals placed on treatment two were vaccinated in two doses, first application 30 days before they arrive on the feedlots and second on the day they arrive on feedlots. After 67 days of experimental period, was calculated the daily gain of live weight in kg/day of the 80 animals and selected 20 animals from each treatment for the slaughter and carcass evaluations, and ten from each group for the meat analyzes. The data were submitted to analysis of variance. Immunocastrated animals showed lower daily weight gain, hot carcass weight, carcass yield, pH, leg thickness, muscle depth, loin muscle area, carcass muscle percentage, shear force and moisture. However, this animals had higher concentration of lactate and cortisol blood, chest depth, fat thickness, finishing degree, a *, b * and c*, liquid loss in thawing process, myofibrillar fragmentation index and ether extract of meat when compared to non-vaccinated bulss. The immunocastration (Bopriva (R)) is an alternative for improving the quality of meat by the higher fat deposition and by the reduction of the shear force of the meat when compared to non-vaccinated bulls.
Influence of immunocastration (Bopriva (R)) in weight gain, carcass characteristics and meat quality of Nellore
Keywords: Finishing degree; gonadotropin-releasing hormone; immunization; tenderness; steers